2015
DOI: 10.1039/c5nr07100c
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected large capacity of ultrafine manganese oxide as a sodium-ion battery anode

Abstract: MnO2 is shown for the first time to be electrochemically active as a conversion anode for Na-ion batteries (NIBs). Space-confined ultrafine (UF)-MnO2, with an average crystal size of 4 nm, synthesized using a porous silicon dioxide templated hydrothermal process exhibits a high reversible sodiation capacity of 567 mA h g(-1), in contrast to the negligible activity shown by the aggregates of larger (14 nm) MnO2 nanocrystallites. The remarkably enhanced sodiation activity of the UF-MnO2 is attributable to its gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 55 publications
(50 reference statements)
1
27
0
Order By: Relevance
“…There are several peaks at 12.7° (110), 18.1° (200), 25.7° (220), 28.8° (310), 37.5° (211), 41.9° (301), 49.8° (411), 56.3° (600), 60.2° (521), 65.2° (002), and 69.5° (541), which can be indexed to a pure phase of MnO 2 (JCPDS 44‐0141). In the case of MnO 2 nanoflowers, the broad peak features with four obvious peaks at 12.7°, 25.7°, 37.5° and 65.2° reveal the nanocrystalline nature of MnO 2 owing to the ultrathin nanopetals with a thickness of about 10 nm, which is similar to previous studies . Figure b displays the nitrogen adsorption/desorption isotherm of MnO 2 nanorods and nanoflowers.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…There are several peaks at 12.7° (110), 18.1° (200), 25.7° (220), 28.8° (310), 37.5° (211), 41.9° (301), 49.8° (411), 56.3° (600), 60.2° (521), 65.2° (002), and 69.5° (541), which can be indexed to a pure phase of MnO 2 (JCPDS 44‐0141). In the case of MnO 2 nanoflowers, the broad peak features with four obvious peaks at 12.7°, 25.7°, 37.5° and 65.2° reveal the nanocrystalline nature of MnO 2 owing to the ultrathin nanopetals with a thickness of about 10 nm, which is similar to previous studies . Figure b displays the nitrogen adsorption/desorption isotherm of MnO 2 nanorods and nanoflowers.…”
Section: Resultssupporting
confidence: 82%
“…Two charge potential plateaus at around 1.2 V and 2.4 V correspond to the formation of MnO 2 , which is consistent with the results of cyclic voltammetry (Figure c). The discharge plateau at close to 0.01 V may be ascribed to non‐Mn‐centered redox reactions, such as the interfacial sodium insertion and surface space‐charge layer, which is similar with the conversion anodes in LIBs …”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Meanwhile, it was proved that nanostructured MnO 2 materials could achieve better electrochemical performance. For instance, space‐confined MnO 2 nanocrystallites exhibited an initial discharge capacity of 567 mAh g −1 . Zhang et al reported that MnO 2 nanorods and nanoflowers could deliver an initial specific capacity of 427 and 488 mAh g −1 , respectively .…”
Section: Introductionmentioning
confidence: 99%
“…The CV curves of as‐prepared MnO 2 on CP were shown in Figure . The reduction process for the 1st cycle was different with the subsequent 4 cycles, which might due to the formation of solid electrolyte interphase (SEI) film in the electrolyte surface and some irreversible structural changes in the 1st cycle . A redox peak at 0.9 V observed for the 1st cycle could be attributed to the electrochemical reaction of carbon paper, which was consistent with the CV curves of pure carbon paper in Figure S2.…”
Section: Introductionmentioning
confidence: 99%